2002
DOI: 10.1093/her/17.3.339
|View full text |Cite
|
Sign up to set email alerts
|

What influences peer-led sex education in the classroom? A view from the peer educators

Abstract: This paper is the second of two presenting data gathered from peer educators in the RIPPLE study-a randomized controlled trial of peer-led sex education in English secondary schools. Peer educators were recruited from Year 12 students (aged 16/17 years) in 13 schools in two successive cohorts in 1997 and 1998. Following a standardized training programme they delivered sex education sessions to Year 9 students (aged 13/14 years). Through analysis of 18 focus group discussions and of post-programme questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 15 publications
(20 reference statements)
4
32
0
Order By: Relevance
“…Our study confirms earlier findings in both theoretical and empirical research that describe peer education as 'successful' in different respects (Harden, Weston, and Oakley 1999;Turner and Shepherd 1999;Mellanby, Rees, and Tripp 2000;Kim and Free 2008). At the same time, we also observed that formal peer education was often developed, organised and controlled by adult professionals (see also Strange, Forrest, and Oakley 2002). Our research suggests however that even if form and content were to be controlled by peer educators, formal contexts may not always be the best contexts to learn from peers.…”
Section: Finding Different Perspectivessupporting
confidence: 91%
“…Our study confirms earlier findings in both theoretical and empirical research that describe peer education as 'successful' in different respects (Harden, Weston, and Oakley 1999;Turner and Shepherd 1999;Mellanby, Rees, and Tripp 2000;Kim and Free 2008). At the same time, we also observed that formal peer education was often developed, organised and controlled by adult professionals (see also Strange, Forrest, and Oakley 2002). Our research suggests however that even if form and content were to be controlled by peer educators, formal contexts may not always be the best contexts to learn from peers.…”
Section: Finding Different Perspectivessupporting
confidence: 91%
“…However another evaluation study [10], conducted on a program based on SLT and Health Belief Model (HBM) [33,35] and geared towards a younger school population, did not reveal changes among the target; slight modifications of risky sexual behaviors were shown by another program [36], which applied some principles of Theory of Reasoned Action [37,38], addressed to middle school students. A recently reported large scale randomized controlled trial was aimed at comparing peer-led with teacherled interventions on sex education in a sample of English secondary schools [39]; the related outcome evaluation is still ongoing and reported results are only concerned with the extensive process evaluation [40,41]. Thus the effectiveness of peer-led educational programs among adolescents at medium-low risk, such as high-school populations, is uncertain and our trial seems to confirm the doubts surrounding the effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…S/he demonstrates behavior that can influence the community norms. The change in the knowledge, behavior and attitude of peer educators have been shown in ripples study [28]. In our study although we don't know how reproductive health behavior of peer educators will be effected, just being a peer educator on a hot topic as reproductive and sexual health should be considered as shaking community norms.…”
Section: Gains Of Peer Educatorsmentioning
confidence: 65%
“…In many studies, superiority of peer education to classical education has been shown [4,26,27], but there are very limited research available on the experiences of peer educators and their preferability [28][29][30].…”
Section: Discussionmentioning
confidence: 99%